Tax Accounting and Livestock in Australia - Fullarton, Lex; Pinto, Dale (The Tax Institute, 2024)
This article provides a comprehensive examination of the tax accounting treatment of livestock in Australian primary production businesses. Contrary to the established practice of categorising all livestock as trading stock, the authors propose an alternative approach, advocating for the recognition of stud or breeding livestock as capital assets. Through a thorough investigation of historical legal cases, particularly FCT v Wade, and legislative changes such as the repeal of s 17 of the Income Tax Assessment Act 1922, the authors challenge the current viewpoint upheld by the ATO since 1951. They suggest practical measures for tax preparers to capitalise breeding animals, enabling them to benefit from CGT concessions. Despite potential challenges in record-keeping and expense deduction, the study emphasises the financial advantages and fairness in aligning tax treatment with the true nature of livestock in primary production businesses.